Um Equilíbrio Delicado: A Dinâmica das Coligações do PT em Eleições Municipais (2000 e 2004) - Luis Felipe Miguel; Carlos Machado (Universidade do Estado do Rio de Janeiro, 2007)
The article analyzes the alliances established by theWorkers' Party (PT) in the 2000 and 2004 elections in all Brazilian municipalities. Over the course of Brazil's current democratic experience, the PT has proven to be the country's most successful party in establishing a "party name". For important segments of the electorate, the PT acquired its identity based on its link to the Left and its rejection of corrupt methods in traditional Brazilian politics. Meanwhile, the Brazilian political system offers strong incentives for a strategy of broad and indiscriminate alliances. Through an analysis of alliances in the municipal elections, centered on government-opposition and Left-Right dichotomies, the article shows how the PT dealt with the opportunities created by (and constraints imposed by) its position in the political camp.